Maritime power in the Black Sea - Sanders, Deborah (Corbett Centre for Maritime Policy Studies series, 2014)
Maritime Power in the Black Sea provides the first comprehensive assessment and evaluation of the comparative maritime power of the six littoral states in the Black Sea - Turkey, Russia, Ukraine, Georgia, Romania and Bulgaria.